2005
DOI: 10.1007/s00280-005-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

The MMP-9 expression determined the efficacy of postoperative adjuvant chemotherapy using oral fluoropyrimidines in stage II or III colorectal cancer

Abstract: The efficacy of postoperative adjuvant chemotherapy using oral fluoropyrimidines such as UFT and 5'-DFUR may not be as great for patients with a tumor positive for MMP-9 having a greater risk to postoperative recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Similarly, in CRC high expression of MMP-2 and MMP-9 may be important in tumor initiation (34,35), development (36), progression, and metastasis (37). Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39). Moreover, high colorectal MMP-9 expression has been implicated in lung metastases (40) and tumor cell resistance to proapoptotic and p53 effects, as well as poor efficacy in postoperative adjuvant chemotherapy (41).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Similarly, in CRC high expression of MMP-2 and MMP-9 may be important in tumor initiation (34,35), development (36), progression, and metastasis (37). Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39). Moreover, high colorectal MMP-9 expression has been implicated in lung metastases (40) and tumor cell resistance to proapoptotic and p53 effects, as well as poor efficacy in postoperative adjuvant chemotherapy (41).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…MMPs (except membrane-type MMPs) are secreted in proenzyme forms and require proteolytic cleavage at the N terminus for activation. The activation cascade for MMPs in the healthy host is closely tied to the fibrinolytic pathway, and activated MMP-3 is believed to be the major physiological activator of most MMPs, including MMP-9 (27,33). While regulation of MMP production in normal cells is tightly controlled and occurs at many levels, the dysregulation of MMPs often associated with disease (27) could be an important consequence of coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Occludin, a tight junction protein that contains a putative MMP cleavage site (8), serves as substrate for both MMP-3 and MMP-9 (18,21). Furthermore, MMP-3 can also degrade tight junction claudins and most extracellular matrix proteins (21,33). Aside from proteolytic effects on endothelial cell tight junctions, MMPs also modulate inflammation by either activating or inactivating cytokines and other inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of MMP-2 and MMP-9 were found to be closely linked to venous and lymph node invasion. Ogata et al (24) reported that MMP-9 expression is related to lymph node metastasis and severe venous invasion. Takeuchi et al (22) reported that RECK expression is significantly associated with lymph node metastasis, Dukes' stage and venous invasion.…”
Section: Discussionmentioning
confidence: 99%